Step pinning and hillock formation in (Al,Ga)N films on native AlN substrates - Schulz, T.; Yoo, S.-H.; Lymperakis, L.; Richter, C.; Zatterin, E.; Lachowski, A.; Hartmann, C.; Foronda, H. M.; Brandl, C.; Lugauer, H. J.; Hoffmann, M. P.; Albrecht, M. (Journal of applied physics, 2022)
The influence of edge-type threading dislocations (TDs) on the epitaxial growth of AlGaN on native AlN substrates was investigated theoretically and experimentally. In the step flow growth regime, we find that pure edge-type TDs cause a pinning of surface steps, resulting in curved step segments. Theoretical calculations reveal that this pinning mechanism is solely mediated by the altered surface potential due the strain field imposed by the TD. Within the curved step segment, the step width is subject to changes resulting in an altered Ga/Al incorporation rate. According to the density functional theory calculation, this effect is related to the different surface diffusion length of Ga and Al and represents a further destabilization mechanism during step flow growth. Another consequence of surface step pinning is the occurrence of areas where the step width is increased. These areas serve as precursors for 2D nucleation due to an increased adatom density. Once nucleated, these nuclei grow along the c-direction via continuous 2D nucleation, while lateral expansion occurs due to adatom incorporation on the m-facets.